2021
DOI: 10.1146/annurev-food-070620-124140
|View full text |Cite
|
Sign up to set email alerts
|

Physiologically Based Modeling of Food Digestion and Intestinal Microbiota: State of the Art and Future Challenges. An INFOGEST Review

Abstract: This review focuses on modeling methodologies of the gastrointestinal tract during digestion that have adopted a systems-view approach and, more particularly, on physiologically based compartmental models of food digestion and host–diet–microbiota interactions. This type of modeling appears very promising for integrating the complex stream of mechanisms that must be considered and retrieving a full picture of the digestion process from mouth to colon. We may expect these approaches to become more and more accu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 109 publications
(120 reference statements)
1
14
0
Order By: Relevance
“…Food structure determines the amount and dynamics of nutrient uptake, as it influences key mechanisms, such as food comminution, food mixing, gastric kinetics, etc . There is increasing evidence that the food matrix plays an important role in the digestion and bioaccessibility of certain phytochemicals, such as polyphenols, anthocyanins, and carotenoids. ,, Moreover, it has been shown that three of the main components that may interfere with phytochemicals digestion are water, fiber, and fat. , For that reason, three food matrices with different structural characteristics: liquid (fruit juice), high fiber (vegetable puree), and high fat content (virgin olive oil) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Food structure determines the amount and dynamics of nutrient uptake, as it influences key mechanisms, such as food comminution, food mixing, gastric kinetics, etc . There is increasing evidence that the food matrix plays an important role in the digestion and bioaccessibility of certain phytochemicals, such as polyphenols, anthocyanins, and carotenoids. ,, Moreover, it has been shown that three of the main components that may interfere with phytochemicals digestion are water, fiber, and fat. , For that reason, three food matrices with different structural characteristics: liquid (fruit juice), high fiber (vegetable puree), and high fat content (virgin olive oil) were selected.…”
Section: Resultsmentioning
confidence: 99%
“…Physiological-based models vary in terms of the number of physiological aspects (i.e., biological mechanisms, organs) considered. Some models only look at the gastrointestinal tract while others consider the whole body [25].…”
Section: Introductionmentioning
confidence: 99%
“…A majority of previous studies has considered the use of computational models to characterize digestive system dynamics by using its physio-chemical properties. For instance, the study [9] provides different modeling methodologies, particularly compartmental models to characterize gastrointestinal tract dynamics during digestion. The study [8] also presents a compartment modeling approach using chemical kinetics in the context of drug administration, while authors in [12] proposes a set of computational models considering different properties of food which include completely soluble, non-soluble and non-degradable types.…”
Section: Introductionmentioning
confidence: 99%